Prevalensi Retinopati Diabetik Pada Penderita Diabetes Melitus Di Klinik Utama Provinsi Maluku - Reubun, Ririn Jihan S; Tamtelatihu, Carmila L; Yunita, Melda (Universitas Tribhuwana Tunggadewi, 2022)
Diabetic retinopathy is still a health problem and may lead to blindness in people with diabetes mellitus. So far, there are no accessible scientific reports regarding the prevalence of diabetic retinopathy in Maluku province. This study aimed to determine the prevalence of diabetic retinopathy in people with diabetes mellitus as prior information about any risk factors for developing diabetic retinopathy. This study was a retrospective descriptive study using medical records of 27 patients seeking treatment at the Eye Clinic Utama in 2020. Univariate data analysis was performed using the Microsoft Excel program. The data is displayed in the form of a frequency distribution graph. The results indicated, the diabetic retinopathy majority suffered by patients aged 56-65 years old (51.9%), dominated in male patients (59.3%), within the common stages of diabetic retinopathy was found in NPDR (85.2%), and the patients had a history of type 2 DM (92.6%). It is recommended for diabetic retinopathy patients to adopt a healthy lifestyle, avoid smoking, and consume alcohol, as well as reduce junk food consumption as a risk factor for the disease.